Ce isotope systematics of island arc lavas from the Lesser Antilles. (1st November 2015) - Bellot, Nina; Boyet, Maud; Doucelance, Régis; Pin, Christian; Chauvel, Catherine; Auclair, Delphine
Abstract: The La-Ce systematics has one of the longest half-lifes ( T 1/2  = 292.5 Ga) of radioactive decay systems used in isotope geochemistry. Variations of the 138 Ce/ 142 Ce ratio are expected to be small and the use of Ce as isotopic tracer requires a very precise measurement. Compared to Sm–Nd studies, the La–Ce decay system can provide additional information about the nature of sediments recycled in subduction zones, because unusually large Ce anomalies relative to the neighboring rare earth elements exist in marine sediments such as fish teeth or hydrothermal deposits. Here, we present a chemical purification technique for Ce, and mass spectrometric technique to perform accurate and reproducible analyses of Ce isotopes of natural samples. We report a large set of Ce isotope data including analysis of 2 Ce reference material solutions (AMES and JMC-304), 2 rock standards (BCR-2 and BHVO-2), 2 chondrites (the carbonaceous chondrite Allende and the enstatite chondrite Sahara 97072), 4 mid-ocean ridge basalts, 30 arc lavas from the Martinique Island and 5 oceanic sediments from DSDP-site 144 drilled on the Demerara rise. The long-term, external precision obtained on the AMES reference material is 80 ppm (2 s.d., 138 Ce/ 142 Ce = 0.0225732 ± 18, n  = 89). However, we note an evolution of isotopic ratios measured in static mode over the duration of this study (33 months). When the reproducibility is calculated from the AMES reference material measured during the same analytical session, it averages 40 ppm. All the 138 Ce/ 142 Ce ratios have been normalized to the AMES value of 0.0225746 (measured in session 7, 2 s.d. = 14 ppm, n  = 8), a session during which the chondritic value has been defined and the peak tailing was negligible. The 138 Ce/ 142 Ce ratio measured for the JMC-304 Ce reference reagent is 0.0225706 ± 9 (2 s.d. = 38 ppm, n  = 10). The analytical precision on natural samples is improved by a factor of about 4 in relation to previous studies on island arcs (Tanaka et al., 1987; Shimizu et al., 1992 ). The 138 Ce/ 142 Ce ratios of the two chondrites are identical within uncertainty and similar to previous determinations done on other meteorites; the average value is 0.0225654 ± 7 (2 s.d. = 32 ppm). Martinique samples show a limited but significant range of variations for 138 Ce/ 142 Ce ratios (∼2 ε -units). The latter ratios correlate well with the Nd isotopes and define a binary mixing between a depleted mantle and subducted sediments that could be similar to those drilled at DSDP-site 144 (Leg 14). The Martinique lavas do not define a single curve in the ε Ce vs. ε Nd diagram, but a band. The apparent scattering can be explained by the involvement of sediments with different Ce isotope compositions and/or variations in the melting process itself such as the effect of melting on the light rare earth element ratios. The Ce isotopic signature of Martinique samples is dominated by the contribution of old terrigeneous sediments. However, according to our mixing models a low contribution of a few percent of marine sediment material in the source of the lavas is undetectable and therefore cannot be definitely excluded. Although the participation of marine sediments in this arc system is not demonstrated, our calculations show that the La–Ce system has a potential as geochemical tracer despite its very long half-life.